Seasonal changes of free amino acids and thermal hysteresis in overwintering heteropteran insect, Pyrrhocoris apterus - Koštál, Vladimír; Renault, David; Rozsypal, Jan (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2011)
Overwintering adults of Pyrrhocoris apterus do not tolerate freezing of their body fluids and rely on a supercooling strategy and seasonal accumulation of polyols to survive at subzero body temperatures. We sampled the adults monthly in the field during the cold season 2008-2009 and found active thermal hysteresis factors (THFs) in hemolymph of winter-sampled adults. The hysteresis between the equilibrium melting and freezing points ranged from 0.18°C to 0.30°C. No signs of THFs activity were found in the autumn- and spring-sampled insects. The total free amino acid pool almost doubled during winter time. The sum concentrations of 27 free amino acids ranged between 35 and 40mM in whole body water and 40-45mM in hemolymph during December-February. Two amino acids, Pro and α-Ala most significantly contributed to the seasonal increase, while Gln showed the most dramatic seasonal decrease. Moderate levels of amino acid accumulation in overwintering P. apterus suggest that they are by-products of protein degradation and pentose pathway activity during the state of metabolic suppression imposed by diapause and low body temperature. Potential colligative effects of accumulated amino acids, extending the supercooling capacity of overwintering P. apterus, are negligible. Non-colligative effects require further study.
Keywords: aminokyseliny; tranzitní teplota; Transition Temperature; Male; kryoprotektivní proteiny; hemolymfa; Water-Electrolyte Balance; hmyzí proteiny; mužské pohlaví; osmolární koncentrace; Animals; ženské pohlaví; roční období; Seasons; Antifreeze Proteins; zvířata; Osmolar Concentration; Insect Proteins; Hemolymph; Female; vodní a elektrolytová rovnováha; Heteroptera; Amino Acids